SPE Americas Unconventional Resources Conference 2012
DOI: 10.2118/155537-ms
|View full text |Cite
|
Sign up to set email alerts
|

Nanopore Structure Analysis and Permeability Predictions for a Tight Gas/Shale Reservoir Using Low-Pressure Adsorption and Mercury Intrusion Techniques

Abstract: The pore structure of unconventional gas reservoirs, despite having a significant impact on hydrocarbon storage and transport, has historically been difficult to characterize due to a wide pore size distribution, with a significant pore volume in the nanopore range. A variety of methods are typically required to characterize the full pore spectrum, with each individual technique limited to a certain pore size range. In this work, we investigate the use of non-destructive, low-pressure adsorption… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 21 publications
(9 citation statements)
references
References 19 publications
0
9
0
Order By: Relevance
“…The pore size distributions illustrate that the shale pore mainly consists of micropores and mesopores. 2,11,14 As the crucial parameters of pore structure, the SSA and pore volume (PV) are dominated by micropores. 2,14 The organic matter was believed to be the major contributor to micropores, 2,4,5,14 while the inorganic matter (e.g., clay 2,4,17,41 and silica 40 ) is the major contributor to nonmicropores (mesopores and macropores).…”
Section: Introductionmentioning
confidence: 99%
“…The pore size distributions illustrate that the shale pore mainly consists of micropores and mesopores. 2,11,14 As the crucial parameters of pore structure, the SSA and pore volume (PV) are dominated by micropores. 2,14 The organic matter was believed to be the major contributor to micropores, 2,4,5,14 while the inorganic matter (e.g., clay 2,4,17,41 and silica 40 ) is the major contributor to nonmicropores (mesopores and macropores).…”
Section: Introductionmentioning
confidence: 99%
“…The pore structure of shale was observed by atomic force microscope, and later research found that the pore diameter of shale oil is 30~400 nm. Loucks et al [27,28] used scanning electron microscopy to find that the pores of shale gas reservoirs are mainly micropores and nanopores. The nanopores are mainly distributed in organic pores, with a small amount dispersed in an inorganic matrix composed of pyrite.…”
Section: Micromechanisms Of Shale Reservoirmentioning
confidence: 99%
“…At the formation scale the Montney is relatively homogeneous and has restricted ranges of grain size (virtually all siltstone), pore size and pore throat size (Clarkson et al 2012). The strong correlation of resistivity and bulk volume water is therefore attributed to electrical conductivity in the Montney tight gas fairway being primarily a response to the volume of hypersaline water in the formation.…”
Section: Bulk Volume Water -Resistivity Relationshipmentioning
confidence: 99%